A Systematic Literature Review of Financial Sustainability - Novitasari, Ni Luh Gde; Yadnyana, I Ketut; Gayatri, Gayatri; Putra, I Nyoman Wijana Asmara (Indonesian Journal of Sustainability Accounting and Management, 2024)
This study aims to examine the progression of financial sustainability by conducting a systematic literature review. It involves critical evaluations of prior research endeavors and endeavors to pinpoint potential directions for future analyses. The data were analyzed using a qualitative approach, which involved examining 27 articles published between 2013 and 2022. Certain reviews have adopted a quantitative method, primarily focusing on micro-finance institutions and banks, there has been limited discourse on the implementation of financial sustainability in both the private and public sectors. The results of this research offer a thorough examination of the development of financial sustainability over the past decade. The review conducted addresses a gap in the existing literature and acts as a valuable roadmap for future investigations into financial sustainability. This research fills a critical gap in existing literature and lays the groundwork for future investigations. Its implications extend to informing decision- makers, practitioners, and policymakers, emphasizing the need for a holistic approach in comprehending the multifaceted aspects of sustainable financial practices. The value of the study offers a nuanced perspective that bridges a gap in existing literature. The findings contribute to informed decision-making for practitioners, policymakers, and academics, fostering a holistic approach to sustainable financial practices.